PEMBERDAYAAN MASYARAKAT MELALUI KAMPUNG SABILULUNGAN BERSIHDALAM MEWUJUDKAN PELESTARIAN LINGKUNGAN - Siti Nadiyah; Deden Sumpena; Indira Sabet Rahmawaty (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
Kampung Sabilulungan Bersih program is a empowermen activities in environmeantal fields. The goal of this research is to know process of conditioning society’s empowerment, efforts implementation a sabilulungan bersih program and a result of the empowerment of the program kampung sabilulungan bersih (saber) to realize environmental preservation in the villag Nagrog. The method used is a qualitative method with descriptive research. The results of this study indicate that: 1). The conditioning process of empowerment kampung sabilulungan bersih program in Nagrog village are participatory by encouraging people to work together to understand, to community, 2). Efforts to kampung sabilulungan bersih program implementation in realizing environmental conservation is by conducting clen Munday, waste management aggregated and bank-select garbage, intelligent hole making organic, sustainable food home areas and planting trees in the area satapok, 3). Results of the kampung sabilulungan bersih program that environmental conditions in Cibiru village increased, people become self-reliant and aware of the importance of protecting the environment.